The Eleventh Commandment - Archer, Jeffrey, 1940- (London HarperCollins, 1998)
Holder of the Congressional Medal of Honor and servant of his country, Connor Fitzgerald is the CIA's most deadly weapon. Only days from his retirement, he comes across an enemy he cannot handle. The enemy is his own boss, the Director of the CIA. And she has only one purpose: to destroy him
Keywords: Assassins -- Intelligence officers -- Political fiction